If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x = 6(x + 5) Reorder the terms: 7x = 6(5 + x) 7x = (5 * 6 + x * 6) 7x = (30 + 6x) Solving 7x = 30 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 7x + -6x = 30 + 6x + -6x Combine like terms: 7x + -6x = 1x 1x = 30 + 6x + -6x Combine like terms: 6x + -6x = 0 1x = 30 + 0 1x = 30 Divide each side by '1'. x = 30 Simplifying x = 30
| 9-4x=10x-16 | | 2(2x-5)(2x-1)=0 | | r/-7-(-5)=-6 | | (x-6)(x-14)=240 | | 6y+27=-3(y-3) | | -2m+9-8(m-1)=8m-(4m-4)-9m+3 | | 4x+1=x^2+20+100 | | 2w^2-2w=35 | | 200*200*400= | | 2p-2(3-4p)=5(p-2)-36 | | 6=3(t-4)+t | | 16x^2+8x+1=x+10 | | 200+200+400= | | 10x+3+8x+19=11 | | x+3/5=11/15 | | 8n+3n=9+12 | | -6x+4x=7x | | u=3(2n+33)+8(n+1) | | z/9+2=20 | | 22/14=x/21 | | 16t^2=73 | | -10(2a-3b)-1(4b-2a)= | | a/3-3(a-2)=2 | | (2x-4x+6x)+3-2+7x+11= | | 6x+11+4x-1=60 | | 3-8x^2-16x^4=0 | | x-48=300 | | (x^2-36)/(2x-12) | | 10+6n=-4+4n | | 0.50x+0.15(30)=44.5 | | 81x^2-27x-4=0 | | 6n-18=4(n-2) |